Contribución de la enseñanza en los procesos metacognitivos y la resolución de problemas matemáticos (2020)
The present study evaluates the contribution of teaching from problem solving to metacognitive processes (Analysis, Planning, Local Monitoring and Global Monitoring) problem solving. The sample consisted of 41 second grade students from a public school in the department of Atlántico (Colombia). Observation was used as the main technique through video recordings of the classes, in addition the Teaching Practice Observation Format and a Semistructured Flexible Interview were used. The participants were selected by means of a nonprobabilistic sampling of intentional type. Regarding the results, the average scores in the metacognitive processes were examined, as well as their relationship at the bivariate level (Pearson's correlation) with the success in solving quantitative reasoning problems. Finally, the predictive variables of success were examined and 43.7% of the Local Monitoring variance was explained by practice at the Start of class and 39.4% of the Global Monitoring variance was explained by practice at Class Closing. . The results obtained in relation to the practice in the classroom are discussed and a series of final recommendations are suggested that contribute to the success in solving mathematical problems to make decisions directed towards the improvement of the curricular processes.